UMP launches MyGift project - UMP, LIB (The New Straits Times Press (M) Bhd., 2016)
KUANTAN: Universiti Malaysia Pahang (UMP) is set to launch the MyGift initiative, which will serve as a channel to receive the university's endowment contributions to facilitate and help the needy.